Ultrastructural analysis of ineffective alfalfa nodules formed by nif::Tn5 mutants of Rhizobium meliloti. - Hirsch, A M (1983)
Ineffective alfalfa nodules formed by Rhizobium meliloti nif::Tn5 mutants were examined by light and electron microscopy. R. meliloti nifH::Tn5 mutants formed nodules that were similar in structure to wild-type nodules except that nifH- bacteroids accumulated a compact, electron-dense body. In contrast to nodules induced by wild type and nifH mutants, nifDK- R. meliloti mutants induced nodules which contained numerous starch grains and prematurely senescent bacteroids. In addition, meristematic activity in nifDK- nodules ceased significantly earlier than in nifH- nodules. All mutant nodules exhibited elevated levels of rough endoplasmic reticulum and Golgi membranes compared to wild-type nodule cells. These elevated levels may reflect either a response to nitrogen starvation in the ineffective nodules or an abnormal synthesis and export of nodule-specific proteins during later developmental stages.